Double‐barrelled wet colostomy formation after pelvic exenteration for locally advanced or recurrent rectal cancer. (3rd November 2016) - Bloemendaal, A. L. A.; Kraus, R.; Buchs, N. C.; Hamdy, F. C.; Hompes, R.; Cogswell, L.; Guy, R. J.
Abstract: Aim: In advanced pelvic cancer it may be necessary to perform a total pelvic exenteration. In such cases urinary tract reconstruction is usually achieved with the creation of an ileal conduit with a urinary stoma on the right side of the patient's abdomen and an end colostomy separately on the left. The potential morbidity from a second stoma may be avoided by the use of a double‐barrelled wet colostomy (DBWC), as a single stoma. Another advantage is the possibility of using a vertical rectus abdominis muscle flap for perineal reconstruction. Method: All patients undergoing formation of a DBWC were included. Result: A DBWC was formed in 10 patients. One patient underwent formation of a double‐barrelled wet ileostomy. Conclusions: In this technical note we present our early experience in 11 cases and a video of DBWC formation in a male patient.